Praktik Manajemen Sumber Daya Manusia dan Kompetensi Karyawan Terhadap Efektivitas Organisasi pada Pegawai Negeri Sipil - Syifa Shofura Widyaputri; Puspita Wulansari (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of human resource management practices and employee competence on organizational effectiveness in Civil Servants (PNS) in the city of Bandung. This research method is a quantitative method by distributing questionnaires as data collection. The results of this study are HR management practices and employee competencies that partially or simultaneously affect organizational effectiveness. In conclusion, the coefficient of determination of HR management practices and employee competence has an effect of 96.3% on organizational effectiveness, while 3.7%, the remainder means that it is influenced by other variables not examined by this study. Keywords: Competency, Practice, Human Resources, Civil Servants